Strength training designed specifically for novice/junior/senior skaters and coaches (2006)
Strength training instructor guidelines, strength training program (to provide the young skater with skill specific and age specific strength training program. The emphasis of the training is to include proper exercise techniques and safety), definition, benefits, strength training protocol (to implement a skating-specific, off-ice strength training program for the purposes of sport injury prevention and enhancement of figure skating performances), strength training program design for the three disciplines of figure skating, skaters checklist for off-ice strength training